Association of ESR1 gene polymorphisms with the susceptibility to Hepatitis B virus infection and the clinical outcomes. Issue 2 (27th January 2023) - Xie, Jiaxin; Ding, Yibo; Li, Xiaopan; Pu, Rui; Liu, Wenbin; Li, Peng; Yin, Jianhua
Abstract: Estrogen receptor alpha ( ESR1 ) has been implicated in the pathological process of Hepatitis B virus (HBV) infection and is probably an important determinant for gender differences. In this study, a total of 975 subjects including 368 healthy controls, 323 hepatocellular carcinoma (HCC) patients with HBsAg positive, and 284 HBV‐infected subjects without HCC were included. Three single nucleotide polymorphisms of ESR1 (rs2234693, rs2077647, rs2228480) were detected to investigate the correlation between ESR1 polymorphisms and the susceptibility to HBV persistence and the clinical outcomes. The association of ESR1 polymorphisms with HCC prognosis was investigated in our cohort enrolling 376 HBV‐HCC patients. The frequency of rs2234693 C allele was lower in chronic Hepatitis B (CHB) and liver cirrhosis (LC) than that in HCC patients in the males (adjusted odds ratio [AOR] = 0.63, 95% confidence interval [CI] = 0.41–0.96). rs2228480 A allele was associated with increased risk of LC (AOR = 2.20, 95% CI = 1.06–4.56) in HBV genotype C, and significantly decreased the risk of HCC recurrence ( p  = 0.010) and ESR1 mRNA level in tumor tissues ( p  = 0.032). Haplotype C‐G‐G was associated with significantly increased risk of HBV persistence (OR = 1.37, 95% CI = 1.08–1.73), while it was opposite for C‐A‐G and T‐G‐G (OR = 0.41, 95% CI = 0.27–0.62; OR = 0.53, 95% CI = 0.32–0.85, respectively). These results imply that combinations of these ESR1 polymorphisms may be valuable for the prediction of HBV persistence.